If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 28 = 14x + -24 Reorder the terms: 28 + 6x = 14x + -24 Reorder the terms: 28 + 6x = -24 + 14x Solving 28 + 6x = -24 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 28 + 6x + -14x = -24 + 14x + -14x Combine like terms: 6x + -14x = -8x 28 + -8x = -24 + 14x + -14x Combine like terms: 14x + -14x = 0 28 + -8x = -24 + 0 28 + -8x = -24 Add '-28' to each side of the equation. 28 + -28 + -8x = -24 + -28 Combine like terms: 28 + -28 = 0 0 + -8x = -24 + -28 -8x = -24 + -28 Combine like terms: -24 + -28 = -52 -8x = -52 Divide each side by '-8'. x = 6.5 Simplifying x = 6.5
| 2.5(x-3)+17x=10.8(x+15) | | 9/2=x/24 | | 200=y/.035 | | 6(5+m)=5(1+m) | | 7(y+2)+5= | | 91u-28=-494 | | (-25)=(-6)a-43 | | 0.50c+(0.40)(600-c)=280 | | x*3+142=x*13-8 | | 2cosx=-3insx | | 5/9=10/k-12 | | 5/9=10/k-2 | | 2(3-2n)=-(n+5) | | P^2-10+c=0 | | 2y=6+4 | | (3x+30)(3x+3)-(2x-1)(2x-1)=0 | | -4-1-1= | | 5(h+2)+3(h+4)=78 | | 3y=5(v-4) | | -2+5-3= | | 9+3x=6-(2x) | | (3x-30)(3x+3)-(2x-1)(2x-1)=0 | | T=C(9+AB)forB | | 2128.88=2100.00(1+0.25) | | 5y^2+8y=13 | | cos(4x)-cos(2x)+sin(3x)=0 | | 2x-3-1= | | (3x-30)(3x+3)-(2x-1)*2=0 | | 5x-57-2x= | | X^4-3x^3+x^2-3x+3=0 | | 35/20=n/4 | | 10=-7x-x^2 |